294 PSORIASIS AND OBESITY. Issue 1 (1st January 2007) - Ahdout, J.; Chiu, M.; Kim, J.
Abstract : Psoriasis is a noncontagious inflammatory skin disease that has been found to lead to the development of obesity. The intent of this study was to identify the factors that contribute to obesity in psoriatic patients. At the time of the interview, the Psoriasis Area and Severity Index (PASI) score was measured to determine the extension of lesions and a questionnaire was administered to assess stress level, exercise, and other medical conditions, such as arthritis. Sixty-six subjects were recruited from UCLA dermatology clinics; 27 subjects were psoriasis patients (average age = 50.33 years, 16 males, 11 females), whereas 39 subjects (average age = 50.49 years, 20 males, 19 females) served as control nonpsoriasis patients. Our preliminary results indicate that psoriasis patients (x = 27.75, SD = 5.81) did not have a significantly higher average body mass index (BMI) than control patients (x = 25.79, SD = 4.25, p = .118). A significant positive correlation was found between BMI and PASI ( r = .45, p = .02). Psoriasis patients with arthritis (x = 28.81, SD = 5.89) were not found to have a significantly higher average BMI than those without arthritis (x = 24.16, SD = 2.42, p = .514). Psoriatic arthritis patients (x = 2.33, SD = 2.40) were not found to exercise significantly more than psoriasis controls (x = 1.97, SD = 2.09, p = .69). Psoriasis patients (x = 2.09 times/week, SD = 2.16) did not report engaging in strenuous exercise significantly less than control patients (x = 1.91 times/week, SD = 2.05, p = .73). Lastly, psoriasis patients did not report significantly more stress (x = 21.26, SD =8.13) than controls (x = 19.84, SD = 8.83, p = .51). According to these preliminary data, there is a significant positive correlation between BMI and increased severity of psoriatic disease as measured by PASI. However, significant data were not found to show that psoriatic patients have a higher BMI, increased stress, and less physical activity than controls. In addition, psoriatic arthritis patients were not found to exhibit a significantly higher BMI and exercise more than psoriasis control patients. Again, these are preliminary results, and we are planning to increase our power in the future by enrolling a total of 200 subjects in our study.